GENDER-BASED APPROACHES TO EFFECTIVE SPEECH ACQUISITION - Kurbanov, Elbek; Pozilov, Bobirjon (International Conference on Linguistics & Translation, 2025)
The pursuit of effective speech skills is a universal goal in education, yet the paths to achieving this competency are not identical. This article argues that a single pedagogical model is fundamentally insufficient to address the complex interplay between gender socialization and language acquisition. It highlights the need for the formal recognition and implementation of gender-based approaches as an essential dimension of effective pedagogy. The term “gender approaches” is defined not as reinforcing essentialist stereotypes but as a sensitive and nuanced framework that recognizes the deeply embedded social and communicative patterns students bring into the learning environment. Drawing on key works in sociolinguistics, educational psychology, and feminist pedagogy, the article examines how gender norms shape communicative confidence, collaborative interaction, and rhetorical self-perception. Furthermore, it argues that by integrating awareness of these gendered dimensions, teachers can not only mitigate participation gaps but also actively empower all learners. The ultimate goal is to develop a pedagogical ecosystem that uses the concept of gender socialization as a tool to unlock the full speech potential of every student, transforming a potential barrier into a powerful educational resource.